HERITABILITAS DAN PEROLEHAN GENETIK PADA BOBOT IKAN NILA HASIL SELEKSI [Heritability and Genetic gain on Weight of Tilapia Resulted Frown Individual Selection] - Nugroho, Estu; Mayadi, Lalu; Budileksono, Sigit (BERITA BIOLOGI, 2017)
Directional-individual selection on tilapia growth had been conducted in West Nusa Tenggara Province. The base population had been constructed through di allele crossing between six tilapia strains i.e. NIRWANA, BEST, SULTANA, Citralada, JATIMBULAN and White Sleman. A total of 150 brood stock pairs were used for spawning with the ratio of female and male parent 1: 1 in net with size of 1x1x1 m. Two hundred larvae Â produced from each spawn pairs were communally reared in a pond for three months. Directional-individual selection was conducted at the size of > 50 grams. The cut-off for minimum selected fish was based on the lowest individual weight of 10% top population. The average value of heritability on body weight was 0.251 for males and 0.258 for the female population. The total value of genetic gain of body weight for four generations was 51.68% for male population and 56.78% for the female population.